Abdomino Pelvic Tuberculosis Versus Advanced Ovarian Malignancy : A Diagnostic Dilemma - Noor, Serajun; Nahar, Nurun; Bilkis, Afroza; Jabin, Taniza (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Pelvic tuberculosis a common infectious cause of human death remains a global health problem, primarily in developing countries .Diagnosis of extra-pulmonary tuberculosis is challenging as it is rarely pinpointed by clinical symptoms, laboratory and radiological findings of low specificity. Pelvic tuberculosis should be considered in young women presented with pelvic mass, ascites and elevated serum CA 125. A series of fourteen cases between the 20 to 70 years are being reported having spectrum of clinical feature and creating diagnostic dilemma. The final diagnosis was made by histopathology after FNAC, laparoscopy or laparotomy are reviewed here. So the aim was formulation of high degree of suspicion aided by intensive investigation for timely diagnosis of genital tuberculosis, to see the response of antituberculer therapy and avoid unnecessary extended surgery. Chatt Maa Shi Hosp Med Coll J; Vol.14 (2); Jul 2015; Page 65-69